Electrolytic capacitor and method for manufacturing the same
Patent Information
- Application Number
- JP2025059360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0011】 本開示によれば、良好な特性を有する電解コンデンサ、特には高容量又はさらには高容量及び低ESRを有する電解コンデンサ、及びその製造方法を提供することができる。
Smart Images

Figure 2026166431000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing the same.
Background Art
[0002] Conventionally, electrolytic capacitors having a solid electrolyte (solid electrolytic capacitors) are known, and further, electrolytic capacitors using a solid electrolyte and a liquid substance (for example, an electrolytic solution) (hybrid type capacitors) are known. In particular, it is known to use a liquid substance such as polyalkylene glycol. Such a capacitor is advantageous, for example, in terms of the capacity appearance rate in initial capacitor characteristics and film repairability. Capacitors using a conductive polymer compound as a solid electrolyte are also known.
[0003] Such a capacitor has a structure in which a capacitor element having a solid electrolyte and further a liquid are sealed in an outer package, but oxidizing substances such as air may enter therein. Heretofore, it has been known to incorporate an antioxidant into a capacitor.
[0004] Non-Patent Document 1 describes producing a polyethylenedioxythiophene (PEDOT):polystyrenesulfonic acid (PSS) aerogel with low thermal conductivity using supercritical carbon dioxide. According to Non-Patent Document 1, it is stated that the electrical conductivity of the PEDOT:PSS aerogel is improved by a crosslinking treatment with divinyl sulfone (DVS).
[0005] Non-Patent Document 2 is a supplementary material of Non-Patent Document 1, and describes the mechanism of the crosslinked structure of PEDOT:PSS by DVS and the influence of various concentrations of DVS on the structural characteristics of the PEDOT:PSS aerogel.
[0006] Non-patent document 3 describes methods for improving the water resistance of PEDOT:PSS, including adding a crosslinking agent that directly chemically bonds with PEDOT:PSS, and compounding it with other hydrophobic polymers. According to non-patent document 3, DVS reacts with nucleophilic compounds such as ethylene glycol, which are included as additives in PEDOT:PSS, to form a crosslinked polymer, and forms a kind of interpenetrating network structure (IPN) in which PEDOT:PSS is incorporated into its network. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] Haruka Goto, et al. “Thermoelectric Properties of Authentic Aerogels Incorporating PEDOT:PSS with Mesoporous Structures Fabricated by Supercritical Drying” ACS Appl.Polym. Mater.2025,7,426-433 [Non-Patent Document 2] Haruka Goto,et al.“Supporting Information” ACS Appl.Polym. Mater.2025,7,426-433 [Non-Patent Document 3] Yukio Kobayashi, "Improved Water Resistance of PEDOT:PSS Film," [online], March 22, 2019, Kobayashi Engineering Office, [Retrieved March 3, 2025], Internet<URL:https: / / www5d.biglobe.ne.jp / ~hightech / column.htm> [Overview of the project] [Problems that the invention aims to solve]
[0008] The concentration of conductive polymer in conductive polymer dispersions or solutions used in the manufacture of electrolytic capacitors containing conductive polymers is relatively low (for example, about 2% by mass). Therefore, conventional methods sometimes fail to efficiently retain the conductive polymer in the capacitor's voids (especially the voids inside the porous body of the anode). Consequently, conventional electrolytic capacitor manufacturing methods may not produce sufficient performance, and multiple fillings may be necessary to prevent this.
[0009] This disclosure aims to provide electrolytic capacitors having good characteristics, in particular electrolytic capacitors having high capacitance or even high capacitance and low ESR, and a method for manufacturing the same. [Means for solving the problem]
[0010] The present invention can solve the above problems in the following embodiments. <Aspect 1> A method for manufacturing electrolytic capacitors, (i) To provide a capacitor element comprising an anode foil, a cathode foil, and a separator between them, each having an oxide film formed on its surface. (ii) Prepare a dispersion or solution of a conductive polymer compound containing a conductive polymer compound and a dopant, and optional secondary dopant. (iii) Adding a divinyl compound to the conductive polymer compound dispersion or solution, (iv) Impregnate the capacitor element with the conductive polymer compound dispersion or solution to which the divinyl compound has been added, and dry it to form a solid electrolyte portion in the void between the anode foil and the cathode foil. including, method. <Aspect 2> The method according to embodiment 1, wherein the conductive polymer compound dispersion or solution contains a compound capable of forming a network structure via a divinyl compound. <Aspect 3> The method according to embodiment 1 or 2, wherein the conductive polymer compound dispersion or solution contains polystyrene sulfonic acid as a dopant. <Aspect 4> The method according to any one of embodiments 1 to 3, wherein the conductive polymer compound dispersion or solution contains a polyol as a secondary dopant. <Aspect 5> The method according to any one of embodiments 1 to 4, wherein the divinyl compound is added to the conductive polymer compound dispersion or solution in an amount of 1.5% to 6.0% by mass. <Aspect 6> The method according to any one of embodiments 1 to 5, wherein the divinyl compound has a molecular weight of 100 to 300. <Aspect 7> The method according to any one of embodiments 1 to 6, wherein the divinyl compound further has a sulfonyl group. <Aspect 8> The method according to any one of embodiments 1 to 7, wherein the divinyl compound comprises divinyl sulfone. <Pattern 9> The method according to any one of embodiments 1 to 8, wherein, after (iv) above, a liquid substance is introduced into the capacitor element on which the solid electrolyte portion is formed, so that the liquid substance is present between the anode foil and the cathode foil. <Aspect 10> An electrolytic capacitor obtained by the method described in any of embodiments 1 to 9. <Aspect 11> An electrolytic capacitor having an anode foil, a cathode foil, and a separator between them, with an oxide film formed on their surfaces, and having a solid electrolyte and an optional liquid substance in the void between the anode foil and the cathode foil, The solid electrolyte portion contains a conductive polymer compound, a dopant, and an optional secondary dopant. The solid electrolyte portion has a structure formed by crosslinking a divinyl compound with a compound capable of forming a network structure via the divinyl compound. Electrolytic capacitor. <Aspect 12> The electrolytic capacitor according to embodiment 11, wherein the compound capable of forming a network structure via the divinyl compound is polystyrene sulfonic acid as the dopant. <Aspect 13> The electrolytic capacitor according to aspect 11 or 12, wherein the compound capable of forming a network structure via the divinyl compound is the polyol as the secondary dopant. <Aspect 14> The electrolytic capacitor according to any one of aspects 11 to 13, wherein the divinyl compound comprises divinyl sulfone. <Aspect 15> The electrolytic capacitor according to any one of aspects 11 to 14, wherein the conductive polymer compound and the dopant form fine particles. [Effects of the Invention]
[0011] According to the present disclosure, it is possible to provide an electrolytic capacitor having favorable characteristics, particularly an electrolytic capacitor having high capacitance, or even high capacitance and low ESR, and a method for producing the same. [Brief Description of the Drawings]
[0012] [Figure 1a] FIG. 1a is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present disclosure. [Figure 1b] FIG. 1b is a schematic perspective view of a capacitor element according to one embodiment of the present disclosure. [Figure 2] FIG. 2 is a schematic cross-sectional view of a main part of the electrolytic capacitor. [Figure 3] FIG. 3 shows the relationship between the added amount of the divinyl compound and the capacitance at 120 Hz. [Figure 4] FIG. 4 shows the relationship between the added amount of the divinyl compound and the E.S.R. at 120 Hz. [Figure 5] FIG. 5 shows the relationship between the added amount of the divinyl compound and the tanδ at 120 Hz. [Figure 6] FIG. 6 shows the relationship between the added amount of the divinyl compound and the E.S.R. at 100 Hz. [Mode for Carrying Out the Invention]
[0013] <<Method for Producing Electrolytic Capacitor>> The method for manufacturing an electrolytic capacitor according to the present invention is: (i) To provide a capacitor element comprising an anode foil, a cathode foil, and a separator between them, each having an oxide film formed on its surface. (ii) Prepare a dispersion or solution of a conductive polymer compound containing a conductive polymer compound and a dopant, and optional secondary dopant. (iii) Adding a divinyl compound to a dispersion or solution of conductive polymer compounds, (iv) Impregnating the capacitor element with a dispersion or solution of a conductive polymer compound to which a divinyl compound has been added, and drying it to form a solid electrolyte portion in the void between the anode foil and the cathode foil. Includes.
[0014] As described above, the concentration of conductive polymer in the conductive polymer dispersion or solution used in the manufacture of electrolytic capacitors containing conductive polymers is relatively low (for example, about 2% by mass). Therefore, conventional methods sometimes failed to efficiently retain the conductive polymer in the voids of the capacitor (especially the voids inside the porous body of the anode). Consequently, conventional electrolytic capacitor manufacturing methods could not produce electrolytic capacitors exhibiting sufficient characteristics, for example, resulting in low capacitance and high resistance. To prevent this, multiple fillings were sometimes required.
[0015] In contrast, in the present invention, in the manufacture of an electrolytic capacitor containing a conductive polymer, a divinyl compound is further added to a dispersion or solution of the conductive polymer compound containing a conductive polymer compound, a dopant, and an optional secondary dopant. A "divinyl compound" is a compound having two vinyl groups (-CH=CH2) in one molecule. This enables high capacitance of the resulting electrolytic capacitor, and in particular, high capacitance and low ESR are achieved.
[0016] Although not limited by theory, it is thought that the added divinyl compound (e.g., divinyl sulfone) interacts with other components present in the conductive polymer compound dispersion or solution (such as compounds constituting the conductive polymer and / or dopants), thereby enhancing the impregnation and / or retention of the conductive polymer compound, and as a result, improving the performance of the resulting electrolytic capacitor.
[0017] The following describes in more detail each step of the manufacturing method according to the present invention.
[0018] <Capacitor element supply process> The present invention provides a capacitor manufacturing method comprising an anode foil, a cathode foil, and a separator between them, each having an oxide film formed on its surface. Detailed embodiments of the components of the capacitor element will be described later. The process of providing this capacitor element is described exemplified below.
[0019] First, an aluminum foil is provided as the anode foil 21. After roughening the surface of the aluminum foil by a surface expansion treatment, a predetermined voltage of 2V to 500V is applied to the roughened surface of the aluminum foil to perform a chemical conversion treatment, thereby forming an oxide film 22 on the surface of the aluminum foil. Then, a capacitor element is fabricated comprising the anode foil 21 having the oxide film 22, a cathode foil 23, and a separator 25 disposed between the anode foil 21 and the cathode foil 23 (see Figure 1(b)). Specifically, the capacitor element 20 is fabricated by overlapping and winding the anode foil 21, which has an uneven surface (rough surface) and on which the oxide film 22 is formed, and the cathode foil 23, which has an uneven surface, via the separator 25. At this time, a lead 30 is connected to the anode foil 21 and a lead 29 is connected to the cathode foil 23.
[0020] Next, the capacitor element 20 is immersed in the chemical conversion solution in the chemical conversion solution tank, and a predetermined voltage (e.g., 100V) is applied between the anode lead 30 and the chemical conversion solution for 5 minutes. This operation repairs oxide film defects present at the edges of the anode foil 21 and any oxide film defects that may be present on the surface.
[0021] As the chemical conversion solution, an aqueous solution of adipic acid, ammonium adipate, boric acid, ammonium borate, phosphoric acid, ammonium dihydrogen phosphate, ammonium hydrogen phosphate, ammonium phosphate, ammonium glutarate, ammonium azelaate, ammonium tartrate, ammonium sebacate, ammonium pimephosphate, ammonium suberate, decanedicarboxylic acid, ammonium decanedicarboxylic acid, long-chain dicarboxylic acid, long-chain ammonium dicarboxylic acid, etc. can be used.
[0022] <Preparation process for conductive polymer compound dispersion or solution> The present invention relates to a method for manufacturing a capacitor, comprising preparing a dispersion or solution of a conductive polymer compound containing a conductive polymer compound, a dopant, and an optional secondary dopant.
[0023] A conductive polymer compound dispersion can be produced, for example, by polymerizing a suspended monomer (e.g., PEDOT monomer) (radical polymerization or oxidative polymerization) to create a conductive polymer compound (e.g., PEDOT polymer) to which dopants and emulsifiers have been added, and then dispersing the conductive polymer compound in a predetermined dispersion medium. The average particle size of the conductive polymer compound can be adjusted by appropriately setting the polymerization reaction conditions (e.g., concentrations of initiators, monomers, polymerization aids, etc., reaction temperature, stirring conditions of the reaction solution, etc.). It can also be adjusted by known grinding treatments (e.g., stirring grinding, vibration grinding, etc.). Furthermore, the particle size can be made uniform by preparative filtration.
[0024] In one embodiment, a dispersion of a conductive polymer compound containing fine particles composed of a conductive polymer compound and a dopant, as well as optional secondary dopants, may be prepared, and a divinyl compound may be added thereto. Details of the fine particles composed of the conductive polymer compound and dopant will be described later.
[0025] According to one embodiment of the present invention, a conductive polymer compound dispersion or solution contains a "compound capable of forming a network structure via a divinyl compound." The "network structure" specifically refers to a three-dimensional higher-order structure formed by the crosslinking of multiple molecules. Examples of the "compound capable of forming a network structure via a divinyl compound" include conductive polymers, dopants (particularly polystyrene sulfonic acid), or polyols optionally added as secondary dopants. In this case, it is believed that an interaction (particularly a crosslinking reaction) is induced between a "compound having two vinyl groups (polymerizable functional groups) in one molecule (divinyl compound)" and a "compound capable of forming a network structure via a divinyl compound," thereby forming a network structure. It is believed that such a network structure suppresses the outflow of conductive polymers from inside the capacitor element and / or maintains a uniform structure between conductive polymers when the solvent is dried after impregnation of the capacitor element with the dispersion or solution. For more information on "compounds capable of forming a network structure via a divinyl compound," please refer to the later description of the electrolytic capacitor according to the present invention (including specific examples of compounds).
[0026] In one preferred embodiment, the dopant is polystyrene sulfonic acid (PSS). Although not limited by theory, in this case, it is thought that the divinyl compound and polystyrene sulfonic acid crosslink and form a network structure. This is thought to suppress the outflow of conductive polymers from inside the capacitor element when the solvent is dried after impregnation with a dispersion or solution, and to maintain a uniform structure between the conductive polymers.
[0027] In another preferred embodiment, a polyol is added as a secondary dopant. Although not limited by theory, in this case, the divinyl compound is thought to crosslink with the polyol, forming a network structure. This is thought to further suppress the outflow of conductive polymers from inside the capacitor element when the solvent is dried after impregnation with the dispersion or solution, and to further maintain a uniform structure between the conductive polymers.
[0028] As a specific example of a method for preparing a conductive polymer compound dispersion, the preparation procedure (a) to (e) for a PEDOT / PSS fine particle dispersion is shown below: (a) Prepare a PEDOT / PSS fine particle dispersion (e.g., 2% by mass) using ethylenedioxythiophene (EDOT) monomer and polystyrene sulfonic acid (PSS). (b) Remove excess cationic and / or anionic components by ion exchange treatment. (c) The process is carried out using a rotary homogenizer or an ultrasonic homogenizer to produce microparticles. (d) Adjust the pH to 2-5 by neutralization treatment. (e) Add a high-boiling point compound to the PEDOT / PSS fine particle dispersion. This may improve conductivity.
[0029] Steps (a) through (e) may be carried out according to conventional methods.
[0030] The content of the conductive polymer compound in the conductive polymer compound dispersion or conductive polymer compound solution may be 0.1 to 10% by mass, 0.2 to 5% by mass, and particularly 0.5 to 3% by mass.
[0031] For dispersions of conductive polymer compounds, for example, water, protic solvents such as alcohols (e.g., methanol, ethanol, 1-propanol, butanol), and mixtures thereof can be used as dispersion media. For solutions of conductive polymer compounds, for example, water, protic solvents such as alcohols (e.g., methanol, ethanol, 1-propanol, butanol), and mixtures thereof can be used as solvents.
[0032] To further improve the conductive properties of the conductive polymer, at least one selected from, for example, glycerol, diglycerol, triglycerol, tetraglycerol, polyglycerol, polyglyceryl ether, diethylene glycol, triethylene glycol, and polyethylene glycol may be added to the conductive polymer dispersion as a secondary dopant. A solid electrolyte can be formed by drying and solidifying the conductive polymer dispersion. These additives can function as a solid electrolyte by being incorporated into the conductive polymer.
[0033] (Conductive polymer compound) Examples of conductive polymer compounds include at least one selected from polythiophene, polypyrrole, and polyaninin, and their derivatives. The conductive polymer compound may be at least one of these. Preferably, the conductive polymer compound is a polymer of EDOT and its derivatives. Particularly preferred conductive polymer compounds are polyethylenedioxythiophene (PEDOT) (especially poly(3,4-ethylenedioxythiophene)).
[0034] (Dopant) The solid electrolyte further contains a dopant. Specific examples of dopants include aromatic sulfonic acids such as benzenesulfonic acid or its derivatives, naphthalenesulfonic acid or its derivatives, and anthraquinonesulfonic acid or its derivatives; polymeric sulfonic acids such as polystyrenesulfonic acid (PSS), sulfonated polyesters, phenolsulfonic acid novolac resins, and copolymers of styrenesulfonic acid with non-sulfonic monomers (such as methacrylic acid esters, acrylic acid esters, unsaturated hydrocarbon-containing alkoxysilane compounds or their hydrolysates); and chain-like sulfones such as methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, and butanesulfonic acid. These may be used individually or in combination of two or more.
[0035] Polystyrene sulfonic acid (PSS) with a weight-average molecular weight of 10,000 to 1,000,000 is preferred. The weight-average molecular weight may be measured by gel filtration chromatography.
[0036] In a particularly preferred embodiment, the solid electrolyte comprises polyethylenedioxythiophene (PEDOT) as a conductive polymer compound and polystyrene sulfonic acid (PSS) as a dopant.
[0037] The conductive polymer compound and dopant may form fine particles (i.e., they may have a particulate shape). The average particle size of the fine particles composed of the conductive polymer compound and dopant may be 1 nm to 1 μm or 1 nm to 600 nm, preferably in the range of 1 nm to 300 nm, or even more preferably in the range of 5 nm to 200 nm (e.g., 20 nm). The average particle size of the fine particles composed of the conductive polymer and dopant can be determined, for example, from the particle size distribution by dynamic light scattering.
[0038] In the capacitor according to this disclosure, the proportion of the conductive polymer compound in the void between the anode foil and the cathode foil may be 0.5 vol% to 40 vol%, or even 1.0 vol% to 20 vol%.
[0039] In one embodiment, the solid electrolyte contains a dopant at a high concentration, and the mass ratio of the conductive polymer compound to the dopant is 1:10 to 1:0.5, or more preferably 1:8 to 1:1, 1:6 to 1:1, or even more preferably 1:5 to 1:1.5. For example, the conductive polymer compound (e.g., PEDOT) may be 10 to 200% by mass, preferably 12.5 to 100% by mass, or more preferably 20 to 67% by mass, relative to the dopant (e.g., PSS).
[0040] (Second Dopant) The solid electrolyte may contain a secondary dopant. The secondary dopant may act as an conductivity enhancer. The secondary dopant is a different compound from the dopant described above. The secondary dopant may be a particle-penetrating liquid (particularly a liquid that penetrates conductive polymer-containing particles), and this liquid may penetrate and fill the inside of the particles (particularly conductive polymer-containing particles), moving the molecular chains of the conductive polymer, thereby promoting stacking of the conductive polymer particles, and consequently improving conductivity. Furthermore, the secondary dopant may have a swelling effect. That is, by containing a secondary dopant, the solid electrolyte constituting the electrolyte portion (for example, fine particles formed from a conductive polymer compound and a dopant) may swell, thereby expanding the internal space of the particles and further improving conductivity. Therefore, the secondary dopant is particularly a swelling agent. The secondary dopant may be a polar organic solvent or organic compound with a boiling point of 150°C or higher, or a liquid polymer compound without a boiling point, such as a polymer having a polyether structure, and may have a weight-average molecular weight of 100 to 10000 (measured by gel filtration chromatography). Specific examples of secondary dopants include polyols, such as glycerol, diglycerol, triglycerol, tetraglycerol, polyglycerol, polyglyceryl ether, diethylene glycol, triethylene glycol, and polyethylene glycol. These can function as solid electrolytes by being incorporated into conductive polymers. As described above, the secondary dopant preferably contains or consists of a polyol. Unlike conventional functional liquids and electrolytes, the secondary dopant exists in a solid electrolyte.
[0041] In an exemplary embodiment, PSS acts as a counterion (Dope agent) that stabilizes the polarons (+holes) of PEDOT formed during the polymerization of EDOT (it is contained in the polymer). Further conductivity is improved by adding high-boiling point solvents such as PEG or glycerol as secondary dopants to this particulate PEDOT / PSS. Although not limited by theory, this phenomenon is thought to be caused by the swelling of PEDOT / PSS particles (imagine a ball-like structure of PSS, with PEDOT partially attached to the threads of PSS) in a solvent, etc., forming a stacking (layered arrangement) interstructure similar to the crystallization of PEDOT, thereby promoting electronic conductivity. The swollen PEDOT / PSS particles then solidify as a solid electrolyte.
[0042] In one embodiment, the mass content of the secondary dopant contained in the capacitor element according to the present disclosure may be 1 to 45 times, or even 2 to 35 times, the total amount of the conductive polymer compound and the dopant.
[0043] The polyol as a secondary dopant is preferably contained in a conductive polymer compound dispersion or conductive polymer compound solution in an amount of 2 to 90% by mass, more preferably 4 to 70% by mass.
[0044] (Divinyl compound addition process) The present invention relates to a method for manufacturing a capacitor, which involves adding a divinyl compound to a dispersion or solution of a conductive polymer compound. This addition may be carried out at room temperature. Stirring may be performed as appropriate after the addition of the divinyl compound.
[0045] In one embodiment, the divinyl compound may be added to the conductive polymer compound dispersion or solution in amounts of 0.1% to 7.0% by mass, 0.7% to 6.0% by mass, 1.0% to 6.0% by mass, 1.5% to 6.0% by mass, or even 2.0% to 5.5% by mass.
[0046] By having a divinyl compound content within this range, it is possible to provide electrolytic capacitors that exhibit relatively high capacitance and low ESR (especially low ESR at low frequencies). In particular, when this divinyl compound content is 1.5% by mass or more, in addition to relatively high capacitance and low ESR at low frequencies, it is possible to provide electrolytic capacitors with reduced tanδ and low ESR at high frequencies.
[0047] In one embodiment, the divinyl compound may have a molecular weight of 100 to 300, or even 100 to 200. A molecular weight that is not excessively large ensures good dispersibility of the divinyl compound in the liquid substance. The molecular weight can be measured by gel filtration chromatography.
[0048] In one embodiment, the divinyl compound may further have a benzene ring and / or a sulfonyl group, particularly a sulfonyl group. This allows the solid electrolyte of the finished capacitor to have relatively good conductivity. In this case, an electrolytic capacitor with particularly good capacitance and low ESR characteristics can also be obtained. Although not limited by theory, it is thought that the electron-withdrawing nature of the sulfonyl group or benzene ring increases the crosslinking reactivity of the vinyl group, thereby yielding an electrolytic capacitor with particularly good characteristics.
[0049] In one embodiment, the divinyl compound may contain or consist of divinyl sulfone. This allows the solid electrolyte of the finished capacitor to have particularly relatively good conductivity.
[0050] In one embodiment of the present disclosure, the divinyl compound according to the present invention may have the structural formula of formula (I). 1 The structure contains at least one of a carbon atom (C), an oxygen atom (O), and a sulfur atom (S), preferably having 0 to 10 carbon atoms, 0 to 5 oxygen atoms, and 0 to 3 sulfur atoms. 1This includes or consists of one of the following: a C1-C10 hydrocarbon group, a benzene ring which may be substituted with a C1-C3 alkyl group, a sulfonyl group, an alkyl group, a siloxane, or a polycyclic aromatic group. 1 This may particularly have a sulfonyl group or a benzene ring, and preferably a sulfonyl group or a benzene ring.
[0051] Preferred divinyl compounds include divinyl sulfone, divinylbenzene, linear hydrocarbon divinyl compounds and their derivatives, such as 1,3-butadiene, 1,4-pentadiene, 1,5-hexadiene, 1,6-heptadiene, 1,7-octadiene, 1,8-nonadien, 1,9-decadien and their derivatives, divinylsilane compounds and their derivatives, such as divinylsilane, dimethyldivinylsilane, divinylpolysiloxane and their derivatives, divinyl ethers and their derivatives, such as 1,4-butanediol divinyl ether, diethylene glycol divinyl ether, cyclohexanedimethanol divinyl ether, triethylene glycol divinyl ether and their derivatives, other divinyl compounds and their derivatives, such as divinylamine, divinyl carboxylate, divinyl sulfide, divinyl methacrylate, divinylacrylamide, divinylnaphthalene, divinylurea, N,N'-methylenebisacrylamide and their derivatives, and compounds obtained by further adding vinyl groups to these divinyl compounds. These compounds may be used individually or in combination of two or more. Particularly preferred divinyl compounds include divinyl sulfone and divinylbenzene.
[0052] [ka]
[0053] The structural formula (II) of divinyl sulfone is shown below.
[0054] [ka]
[0055] The structure (III) of divinylbenzene (DVB) is shown below: [ka]
[0056] <Solid electrolyte part formation process> The present invention's method for manufacturing a capacitor includes impregnating a capacitor element with a dispersion or solution of a conductive polymer compound containing a divinyl compound, and then drying it to form a solid electrolyte portion in the gap between the anode foil and the cathode foil.
[0057] For example, a capacitor element is immersed in a conductive polymer compound dispersion or conductive polymer compound solution using an introduction tank. Then, the capacitor element is removed from the conductive polymer compound dispersion or solution and heat-treated to form an electrolyte between the anode foil and the cathode foil. This operation can be repeated multiple times, thereby increasing the amount of solid electrolyte packed in.
[0058] The solid electrolyte portion can be formed by an immersion impregnation method. Specifically, a conductive polymer compound dispersion (for example, a conductive polymer compound concentration of 2% by mass) is filled into an introduction tank, and then the capacitor element is immersed in the conductive polymer compound dispersion. Next, the capacitor element is removed from the introduction tank, and then the capacitor element is heat-treated. This allows the solid electrolyte to be introduced into the gap between the anode foil 21 and the cathode foil 23, thereby forming an electrolyte portion on the oxide film.
[0059] Furthermore, in order to increase the proportion of solid electrolyte in the voids, the number of repetitions of the above operation can be increased, and / or the polymer concentration in the conductive polymer compound dispersion can be increased. On the other hand, in order to decrease the proportion of solid electrolyte in the voids, the number of repetitions of the above operation can be decreased, and / or the polymer concentration in the conductive polymer compound dispersion can be decreased.
[0060] Detailed descriptions of the solid electrolyte will be provided later.
[0061] The impregnated capacitor elements may be dried at a temperature of 100°C to 180°C for 10 to 120 minutes. This drying process removes at least some of the liquid components contained in the solid electrolyte.
[0062] (Introduction process of liquid substance) The method for manufacturing an electrolytic capacitor according to this disclosure may optionally include a step of introducing a liquid substance into the capacitor element (particularly the gap between the anode foil and the cathode foil).
[0063] In one embodiment, a liquid substance is introduced into the capacitor element in which a solid electrolyte portion is formed, thereby causing the liquid substance to be present between the anode foil and the cathode foil.
[0064] The liquid substance introduced in this way can penetrate the formed solid electrolyte, thereby further improving the conductivity of the conductive polymer compound. In this case, the capacitor's characteristics may also improve, resulting in lower ESR (low resistance) and higher capacitance, as well as delayed degradation (longer lifespan) due to improved conductivity. Although there is no intention to limit the theory, it is thought that the liquid substance that penetrates the solid electrolyte (e.g., a high-boiling-point compound such as ethylene glycol) is absorbed by the fine particles of the conductive polymer compound, promoting the formation of the arrangement structure of the conductive polymer compound, and consequently improving conductivity.
[0065] In this process, for example, a liquid substance 27 is introduced into the void between the anode foil 21 and the cathode foil 23 so as to surround the solid electrolyte, and so that the proportion of the liquid substance 27 in the void is within the range of 10 vol% to 99 vol%.
[0066] When filling with liquid material by immersion impregnation, the liquid material may be introduced into the void by filling the introduction tank with liquid material and then immersing the capacitor element in the liquid material.
[0067] Examples of liquid substances include glycol compounds, such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, and other polyethylene glycols, as well as their derivatives; glycerol and diglycerol, as well as their derivatives; γ-butyrolactone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, and dimethylformamide. These may be used individually or in combination of two or more. Detailed embodiments of the liquid substances will be described later.
[0068] An electrolytic capacitor can be manufactured by enclosing a capacitor element having a solid electrolyte, manufactured through the above process, in a case.
[0069] This process (assembly and sealing process) is described exemplified below. In the assembly and sealing process, for example, the sealing material 40 is attached to the capacitor element 20, and after inserting the capacitor element 20 into the metal case 10, the metal case 10 is crimped near the open end of the metal case 10. As the sealing material 40, for example, isobutylene-isoprene rubber (IIR) can be used. Instead of isobutylene-isoprene rubber (IIR), rubber materials such as ethylene-propylene terpolymer (EPT), EPT-IIR blend rubber, silicone rubber, or rubber composite materials made by bonding resin and rubber such as phenolic resin (Bakelite), epoxy resin, or fluororesin can be used for sealing. Furthermore, the sealing rubber surface crimped with the sealing material can be coated with epoxy resin or the like by potting to enhance airtightness, sealing strength, and heat resistance. After that, an aging process is carried out by applying a predetermined voltage in a high-temperature atmosphere. This completes the electrolytic capacitor 1 according to the embodiment.
[0070] <<Electrolytic capacitor containing conductive polymer>> This disclosure includes the following electrolytic capacitors: An electrolytic capacitor having an anode foil, a cathode foil, and a separator between them, with an oxide film formed on their surfaces, and having a solid electrolyte and an optional liquid substance in the void between the anode foil and the cathode foil, The solid electrolyte portion contains a conductive polymer compound, a dopant, and an optional secondary dopant. The solid electrolyte portion has a structure formed by crosslinking a divinyl compound with a compound that can form a network structure via the divinyl compound. Electrolytic capacitor.
[0071] For details of each component in this embodiment (conductive polymer compound, dopant, secondary dopant, divinyl compound, etc.), please refer to the description of the manufacturing method of the present invention above. The solid electrolyte may have, for example, the following composition: Conductive polymer compounds in a concentration of 0.1 to 15.0% by mass, particularly 0.2 to 10.0% by mass, and even more specifically 0.3 to 5.0% by mass. 0.2-40.0 mass% dopants, especially 0.3-20.0 mass%, and even 0.4-10.0 mass%, 50-99% by mass, especially 60-98% by mass of secondary dopants, Divinyl compounds in amounts of 0.01 to 30.0% by mass, particularly 0.02 to 20.0% by mass, and even more specifically 0.1 to 10.0% by mass.
[0072] "Compounds that can form a network structure via divinyl compounds" are, in particular, compounds that can form a three-dimensional higher-order structure by being crosslinked by the two vinyl groups of the divinyl compound.
[0073] Examples of "compounds that can form a network structure via divinyl compounds" include compounds having a hydroxyl group (-OH), a vinyl group (-CH=CH2), a styrene group, a sulfonic acid group (-SO3H), and an amino group (-NH2). These may be one type or a combination of two or more types. More specific examples of compounds include compounds having two or more (especially two) hydroxyl groups in one molecule, compounds having one to two (especially one) vinyl groups in one molecule, and compounds having one to two (especially one) sulfonic acid groups in one molecule.
[0074] Examples of compounds that can form a network structure via divinyl compounds include polyols, styrene, and polystyrene sulfonic acid.
[0075] In one embodiment, polystyrene sulfonic acid as a dopant is a compound that can form a network structure via a divinyl compound.
[0076] In one embodiment, a polyol acting as a secondary dopant is a compound that can form a network structure via a divinyl compound.
[0077] In one embodiment, the compounds that can form a network structure via a divinyl compound are polystyrene sulfonic acid as a dopant and a polyol as a secondary dopant.
[0078] In one embodiment, the divinyl compound may include or consist of divinyl sulfone and / or divinylbenzene.
[0079] Such capacitors can be manufactured, for example, by the manufacturing method described above according to the present invention.
[0080] The following are preferred embodiments of the electrolytic capacitor of the present invention: In solid electrolytes, the divinyl compound is present in an amount of 1 to 600 parts by weight, 10 to 500 parts by weight, 50 to 450 parts by weight, or even 75 to 400 parts by weight, relative to 100 parts by weight of the total of the conductive polymer compound and the dopant. The divinyl compound has a molecular weight of 100 to 300, or even 100 to 200.
[0081] <Anode foil> The anode foil may be formed from a valve metal such as aluminum, tantalum, or niobium.
[0082] The anode foil has an oxide film on its surface. For example, an oxide film can be formed on the surface of the anode foil by roughening the surface by etching according to a known method and then by a chemical conversion treatment.
[0083] <Cathode Foil> The cathode foil, like the anode foil, may be formed from a valve metal such as aluminum, tantalum, or niobium. The cathode foil may also be formed from an aluminum alloy containing copper.
[0084] The cathode foil may have an oxide film formed on its surface. For example, the surface of the cathode foil may be roughened by etching, similar to the anode foil, and then an oxide film may be formed by natural oxidation. Alternatively, the cathode foil may be subjected to a chemical conversion treatment at a desired voltage (e.g., 2V), which may also form an oxide film.
[0085] <Separator> Preferably, the separator is made of conductive polymer particles, cellulose fibers that are chemically compatible with water-soluble polymers, or synthetic resins such as nylon, PET, and PPS that have excellent heat resistance. For example, heat-resistant cellulose paper or heat-resistant flame-retardant paper can be used. More specifically, examples of separators include cellulose and mixed papers such as kraft, Manila hemp, esparto, hemp, and rayon; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and their derivatives; polytetrafluoroethylene resins; polyvinylidene fluoride resins; vinylon resins; polyamide resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide resins; polyethylene resins; polypropylene resins; trimethylpentene resins; polyphenylene sulfide resins; acrylic resins; and polyvinyl alcohol resins. These resins can be used individually or in mixtures.
[0086] <Solid electrolyte section> The solid electrolyte portion, composed of a solid electrolyte, exists in the void between the anode foil and the cathode foil. In this disclosure, "the void between the anode foil and the cathode foil" includes not only "the void between the anode foil and the separator and the void between the cathode foil and the separator," but also "the void between fibers within the separator." Furthermore, "the void between the anode foil and the cathode foil" also includes "the void in etching pits (recesses) formed on the surface of the anode foil or cathode foil by roughening through etching."
[0087] The solid electrolyte portion, composed of a solid electrolyte, is in at least partial contact with the oxide film formed on the surface of the anode foil. The solid electrolyte portion contains a conductive polymer compound and a dopant.
[0088] The solid electrolyte portion may take various forms, for example, a continuous, uniform thick or thin layer, a film, or an aggregate of fine particles, or a network of fine particle chains. In particular, the solid electrolyte portion may take the form of a layer of fine particles composed of fine particles containing a conductive polymer compound (and optionally a dopant).
[0089] The solid electrolyte portion is in direct contact with the oxide film of the anode foil, at least partially, and in direct contact with the metal surface and / or oxide film of the cathode foil, at least partially.
[0090] <Liquid substances> The electrolytic capacitor according to this disclosure may contain a liquid substance. Preferably, the liquid substance is present between the anode foil and the cathode foil. In particular, the liquid substance may be present so as to surround the solid electrolyte (particularly fine particles containing a conductive polymer compound that constitute the solid electrolyte portion).
[0091] From the viewpoint of film repair, an electrically neutral and polar liquid substance (solvent) is preferred. This solvent is less affected by the repulsion due to the surface charge of the PEDOT / PSS particles, so it penetrates into the interior and even moves to the outside of the particles. Furthermore, since an oxygen-containing polar solvent can be supplied, film formation is performed with high efficiency. Examples of such solvents include proton-based high-boiling-point polar solvents with a boiling point of 150°C or higher, such as ethylene glycol, diethylene glycol, triethylene glycol, glycerol, and their derivatives, as well as polymer solutions of polyethylene glycol, polyalkylene glycol, polyglycerol, polyoxyalkylene polyglyceryl ether, and their derivatives.
[0092] In the capacitor according to this disclosure, the proportion of liquid material in the gap between the anode foil and the cathode foil may be 10 vol% to 99 vol%, particularly 50 vol% to 99 vol%, or even 70 vol% to 99 vol%.
[0093] The liquid substance is not particularly limited, but may include, for example, organic solvents, especially polymeric organic solvents. The liquid substance may include, for example, water, hydrophilic polymer compounds, components having hydroxyl groups, such as polyoxyalkylenes and their derivatives (polyglycerols), water-soluble polyurethanes, water-soluble polyesters, water-soluble polyamides, water-soluble polyimides, water-soluble polyacrylics, water-soluble polyacrylamides, water-soluble silicones, polyvinyl alcohols, polyacrylic acid, or mixtures thereof.
[0094] In particular, the components of the liquid substance include glycol compounds, such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, and other polyethylene glycols, as well as their derivatives, glycerol and diglycerol, as well as their derivatives, γ-butyrolactone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, and dimethylformamide. These may be used individually or in combination of two or more. Of these, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, other polyethylene glycols, and their derivatives are preferred, with ethylene glycol and diethylene glycol being the most preferred. When ethylene glycol and / or diethylene glycol are used as the liquid substance, electrolytic capacitors with particularly good reflow characteristics can be obtained.
[0095] A liquid substance is, for example, a liquid that can hold acidic and basic components. In particular, a liquid substance is a solvent in which acidic and basic components can be dissolved as solutes.
[0096] In particular, the liquid substance contains glycol compounds (particularly ethylene glycol and / or diethylene glycol) in a total proportion of 30% to 99% by mass, 50 to 95% by mass, or even 60% to 80% by mass. In one particular embodiment, the liquid substance also contains glycol compounds (particularly ethylene glycol and / or diethylene glycol) in a total proportion of 90% to 100% by mass, 90 to 99.9% by mass, or even 95% to 99.5% by mass.
[0097] (water) The liquid substance may contain water.
[0098] When the liquid substance present in the void between the anode foil and the cathode foil contains "water," particularly good effects can be obtained in reducing the defect density of the oxide film and reducing leakage current.
[0099] The water content may be 0% to 10% by mass relative to the liquid substance, preferably 0.1% to 10% by mass, and more preferably 0.5% to 5% by mass. When the water content is within this range, the effect of repairing defects in the oxide film can be sufficiently obtained, and adverse effects caused by excessive water content (such as expansion of the capacitor that may occur when used for a long period of time in a high-temperature environment) can be avoided or suppressed.
[0100] Furthermore, when an electrolytic capacitor contains a liquid substance, it can be specifically referred to as a hybrid electrolytic capacitor.
[0101] The liquid substance may contain acidic and basic components. These acidic and basic components are different substances from the amphoteric compounds according to the present invention described above, and do not satisfy the above requirements for amphoteric compounds.
[0102] Examples of acidic components include organic acids, inorganic acids, and complex compounds thereof.
[0103] Examples of organic acids include carboxylic acids, phenols, and sulfonic acids. Examples of carboxylic acids include formic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, sulfosalicylic acid, maleic acid, adipic acid, benzoic acid, triylic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcinic acid, phloroglucinic acid, gallic acid, and citric acid.
[0104] Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid.
[0105] Examples of complex compounds of organic and inorganic acids include borodisalicylic acid, borodisuoic acid, and borodiglycolic acid.
[0106] The acidic components described above may be used individually or in combination of two or more.
[0107] The acidic component is contained, for example, at a concentration of 2.6% to 20% by mass relative to the liquid substance.
[0108] The basic component may be one or more selected from amines, amidines, and ammonia, and is preferably an amine.
[0109] The basic component may be present in an amount of 0.2% to 20% by mass relative to the liquid substance.
[0110] <Configuration of the resulting electrolytic capacitor 1> Figures 1a and 1b are diagrams illustrating the electrolytic capacitor 1 obtained by the method of the present invention. Figure 1a is a cross-sectional view of the electrolytic capacitor 1, and Figure 1b is a perspective view of the capacitor element 20.
[0111] Figure 2 is a cross-sectional view of the main part of the electrolytic capacitor 1 obtained by the method of the present invention, illustrating its main components.
[0112] The electrolytic capacitor 1 obtained by the method of the present invention is a wound electrolytic capacitor, and as shown in Figure 1a, comprises a bottomed cylindrical metal case 10, a capacitor element 20, and a sealing material 40.
[0113] The bottom of the metal case 10 is nearly circular in shape, and a valve (not shown) is provided near the center. This structure allows the valve to break and release the internal pressure to the outside when the internal pressure rises. The side of the metal case 10 is erected almost perpendicular to the outer edge of the bottom. The opening of the metal case 10 is sealed with a sealing material 40, and the two leads 29 and 30 of the capacitor element 20 are led out to the outside through through holes provided in the sealing material 40.
[0114] The capacitor element 20 is housed inside the metal case 10 and, as shown in Figures 1(b) and 2, comprises an anode foil 21, a cathode foil 23, and a separator 25 disposed between the anode foil 21 and the cathode foil 23, with the anode foil 21 and cathode foil 23 overlapping and wound together via the separator 25.
[0115] In the embodiment shown in Figure 2, the anode foil 21 and cathode foil 23 each have oxide films 22 and 24 on their surfaces, respectively. A solid electrolyte 26, composed of fine particles of a conductive polymer compound / dopant, is placed in contact with the oxide film 22 on the surface of the anode foil 21, forming a solid electrolyte portion. In addition, in the embodiment shown in Figure 2, a liquid substance 27 containing a liquid material is introduced between the anode foil 21 and the cathode foil 23, and the liquid substance 27 surrounds the solid electrolyte 26 made of the conductive polymer compound.
[0116] According to the present invention, for example, the dopant constituting the solid electrolyte 26 and the divinyl compound may crosslink to form a network structure. Furthermore, according to the present invention, if the solid electrolyte 26 contains a polyol, the polyol and the divinyl compound may crosslink to form a network structure. [Examples]
[0117] Embodiments of the present invention will be described in more detail below with reference to examples. The following examples and comparative examples are not intended to limit the present invention.
[0118] <<Examples 1-4 and Comparative Example 1>> In Examples 1-4 and Comparative Example 1, the initial characteristics of electrolytic capacitors manufactured with (or without) divinyl compounds added in various amounts were evaluated.
[0119] <Example 1> (Manufacturing of electrolytic capacitors) In Example 1, divinyl sulfone was used as the divinyl compound. To manufacture the electrolytic capacitor, an aqueous solvent dispersion was prepared containing conductive polymer compound fine particles composed of 2.0% by mass of PEDOT and PSS and 15% by mass of diglycerol as a secondary dopant. 0.5% by mass of divinyl sulfone was added to this dispersion. Commercially available reagents were used.
[0120] This conductive polymer compound dispersion was impregnated into a capacitor element. Specifically, an aluminum anode foil and an aluminum cathode foil, each having a voltage-resistant coating corresponding to the capacitor's rated voltage, were wound together via a cellulose separator to create a capacitor element. The conductive polymer compound dispersion was then vacuum-impregnated into this element to form a solid electrolyte between the anode foil and the cathode foil. After drying, an electrolytic capacitor according to Example 1 was obtained.
[0121] (Measurement of initial characteristics) The characteristics of the electrolytic capacitor obtained in Example 1 were measured after aging treatment and defined as the initial characteristics. Specifically, a KEYSIGHT E4980A Precision LCR Meter was used to measure capacitance (Cap), ESR at 120Hz, tanδ at 120Hz, and ESR at 100Hz. The results are shown in Figures 3 to 6.
[0122] <Example 2> An electrolytic capacitor according to Example 2 was manufactured in the same manner as in Example 1, except that divinyl sulfone as a divinyl compound was added to the dispersion at a concentration of 1.0% by mass. The initial characteristics were then measured and evaluated. The results are shown in Figures 3 to 6.
[0123] <Example 3> An electrolytic capacitor according to Example 3 was manufactured in the same manner as in Example 1, except that divinyl sulfone as a divinyl compound was added to the dispersion at a concentration of 3.0% by mass. The initial characteristics were measured and evaluated. The results are shown in Figures 3 to 6.
[0124] <Example 4> An electrolytic capacitor according to Example 4 was manufactured in the same manner as in Example 1, except that divinyl sulfone as a divinyl compound was added to the dispersion at a concentration of 5.0% by mass. The initial characteristics were measured and evaluated. The results are shown in Figures 3 to 6.
[0125] <Comparative Example 1> An electrolytic capacitor according to Comparative Example 1 was manufactured in the same manner as in Example 1, except that a divinyl compound was not added. The initial characteristics were then measured and evaluated. The results are shown in Figures 3 to 6.
[0126] <Result> Figure 3 shows the relationship between the amount of divinyl compound added and the capacitance at 120 Hz. All of the electrolytic capacitors in Examples 1 to 4 have a higher capacitance at 120 Hz compared to Comparative Example 1.
[0127] Figure 4 shows the relationship between the amount of divinyl compound added and the ESR at 120 Hz. All of the electrolytic capacitors in Examples 1 to 4 have a reduced ESR at 120 Hz compared to Comparative Example 1.
[0128] Figure 5 shows the relationship between the amount of divinyl compound added and tanδ at 120 Hz. In particular, all of the electrolytic capacitors in Examples 2 to 4 have a reduced tanδ at 120 Hz compared to Comparative Example 1.
[0129] Figure 6 shows the relationship between the amount of divinyl compound added and the ESR at 100 Hz. In particular, all of the electrolytic capacitors in Examples 3 and 4 have a reduced ESR at 100 Hz compared to Comparative Example 1.
[0130] In particular, in Examples 3 and 4, where the amount of divinyl sulfone added to the dispersion was 3.0 or 5.0% by mass, particularly excellent volume, as well as particularly excellent tanδ and low ESR properties, were observed. [Explanation of Symbols]
[0131] 1 Electrolytic capacitor 10 Exterior 20 Capacitor elements 21 Anode foil 22, 24 Oxide film 23 Cathode foil 25 Separators 26 Solid electrolyte 27. Liquid substances 29, 30 Lead 40 Sealing material
Claims
1. A method for manufacturing electrolytic capacitors, (i) To provide a capacitor element comprising an anode foil, a cathode foil, and a separator between them, each having an oxide film formed on its surface. (ii) Prepare a dispersion or solution of a conductive polymer compound containing a conductive polymer compound and a dopant, and optional secondary dopants. (iii) Adding a divinyl compound to the conductive polymer compound dispersion or solution, (iv) Impregnate the capacitor element with the conductive polymer compound dispersion or solution to which the divinyl compound has been added, and dry it to form a solid electrolyte portion in the void between the anode foil and the cathode foil. including, method.
2. The method according to claim 1, wherein the conductive polymer compound dispersion or solution contains a compound capable of forming a network structure via a divinyl compound.
3. The method according to claim 1 or 2, wherein the conductive polymer compound dispersion or solution contains polystyrene sulfonic acid as a dopant.
4. The method according to claim 1 or 2, wherein the conductive polymer compound dispersion or solution contains a polyol as a secondary dopant.
5. The method according to claim 1 or 2, wherein the divinyl compound is added in an amount of 0.5% to 6.0% by mass relative to the conductive polymer compound dispersion or solution.
6. The method according to claim 1 or 2, wherein the divinyl compound has a molecular weight of 100 to 300.
7. The method according to claim 1 or 2, wherein the divinyl compound further has a sulfonyl group.
8. The method according to claim 1 or 2, wherein the divinyl compound comprises divinyl sulfone.
9. The method according to claim 1 or 2, further comprising, after (iv) above, introducing a liquid substance into the capacitor element on which the solid electrolyte portion is formed, so that the liquid substance is present between the anode foil and the cathode foil.
10. An electrolytic capacitor obtained by the method described in claim 1 or 2.
11. An electrolytic capacitor having an anode foil, a cathode foil, and a separator between them, with an oxide film formed on their surfaces, and having a solid electrolyte and an optional liquid substance in the void between the anode foil and the cathode foil, The solid electrolyte portion contains a conductive polymer compound, a dopant, and an optional secondary dopant. The solid electrolyte portion has a structure formed by crosslinking a divinyl compound with a compound capable of forming a network structure via the divinyl compound. Electrolytic capacitor.
12. The electrolytic capacitor according to claim 11, wherein the compound capable of forming a network structure via the divinyl compound is polystyrene sulfonic acid as the dopant.
13. The electrolytic capacitor according to claim 11 or 12, wherein the compound capable of forming a network structure via the divinyl compound is a polyol as the secondary dopant.
14. The electrolytic capacitor according to claim 11 or 12, wherein the divinyl compound comprises divinyl sulfone.
15. The electrolytic capacitor according to claim 11 or 12, wherein the conductive polymer compound and the dopant form fine particles.